2021
DOI: 10.1177/21582440211056624
|View full text |Cite
|
Sign up to set email alerts
|

Sans Forgetica is Not the “Font” of Knowledge: Disfluent Fonts are Not Always Desirable Difficulties

Abstract: Subsequent recall is improved if students try to recall target material during study (self-testing) versus simply re-reading it. This effect is consistent with the notion of “desirable difficulties.” If the learning experience involves difficulties that induce extra effort, then retention may be improved. Not all difficulties are desirable, however. Difficult-to-read ( disfluent) typefaces yield inconsistent results. A new disfluent font, Sans Forgetica, was developed and alleged to promote deeper processing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…There is indeed evidence that words with 20% scrambled letters benefited recognition [10]. Our reasoning could also explain the consistent null results found with reading passages ( [23,30] Experiment 3, [31][32][33])-SF only creates letter-level difficulty, once the word(s) are identified/read, SF does not interfere or support the memory for the ideas those words conveyed. This letter-level difficulty could also be why SF made non-contextual errors (i.e., typos) in passages from Cushing & Bodner [35] more difficult to detect.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…There is indeed evidence that words with 20% scrambled letters benefited recognition [10]. Our reasoning could also explain the consistent null results found with reading passages ( [23,30] Experiment 3, [31][32][33])-SF only creates letter-level difficulty, once the word(s) are identified/read, SF does not interfere or support the memory for the ideas those words conveyed. This letter-level difficulty could also be why SF made non-contextual errors (i.e., typos) in passages from Cushing & Bodner [35] more difficult to detect.…”
Section: Discussionsupporting
confidence: 62%
“…To our knowledge, there have only been thirteen studies that investigated whether SF can be a desirable difficulty. These studies compare performance between SF and a fluent font, typically Arial, sometimes Times New Roman (e.g., [23]). SF seems to benefit recognition (greater sensitivity d') of studied words ( [24] Experiment 1-only when a test was not expected) but there are also mixed findings [25] and null results [26].…”
Section: Existing Research On Sfmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining how using a perceptually difficult-to-process typeface with an increased desirable difficulty designed specifically to reduce legibility, such as Sans Forgetica, found either no processing or memory benefit of such typefaces or even yielded a memory cost (Geller et al, 2020;Taylor et al, 2020;Wetzler et al, 2021;Cushing and Bodner, 2022;Maxwell et al, 2022). However, there is also a whole series of studies which showed that poorer fluency of the text or desired difficulty in the fluency of the text resulted in better processing of the text and consequently in better memorisation of the read content (Diemand-Yauman et al, 2011;Macdonald and Lavic, 2011;Bjork et al, 2013;Halin, 2016;Pieger et al, 2016).…”
Section: Text Comprehension and Memorisationmentioning
confidence: 99%
“…Hagtvedt (2011) suggested that companies try to deliberately create an innovative image in order to attract consumers’ attention to their advertisements even though the incomplete text used in these advertisements may decrease their consumers’ trust. In addition, Wetzler et al (2021) introduced the following hypothesis: if the learning experience involves difficulties that induce extra effort, then retention may be improved. With the aim to enhance learning, a new disfluent typeface, Sans Forgetica, was developed and alleged to promote deeper processing and improve learning.…”
Section: Introductionmentioning
confidence: 99%